Developing technology of remediation of oil-contaminated soils - Shevchyk, Lesya; Romaniuk, Olga (Видавництво Львівської політехніки, 2013)
Abstract – The results of developing technologies for cleaning of soils from oil pollution on the example of Boryslav are shown. The prospects of tree species for the remediation of oil-contaminated soils are studied. The best results of cleaning oil contaminated soils with the application of Hippophae rhamnoides L. plants were obtained. It is a promising measure for restoring the oil-contaminated soils, attractive both from environmental and economical point of view.
Keywords: oil-contaminated soils; technologies of remediation; a phytoremediation; Hippophae rhamnoides L.; a phytotoxicity; secondary fuel